FORUM KEMITRAAN POLISI DAN MASYARAKAT (FKPM): SEBUAH PENDEKATAN PERPOLISIAN MASYARAKAT UNTUK MEMBANGUN CITRA POLISI - Ary Wahyono (Jurnal Masyarakat dan Budaya, 2009)
The traditional concept of police has created an image that police has not seen community as major partner in policing. Therefore, community policing approach is formulated. Community policing tries to control crime using preventive approach, which proactively done by good partnership between the police and the community. It does not depend on modern technology, machines and knowledge based anymore. The concept of community policing has shown that networking between humans is a source to control crime. Community policing as a philosophy, actually has already implemented in everyday life because that what citizen desired. This is why the establishment of FKPM has greatly welcomed by the community. From the observation in many local regions, the establishment of FKPM has been given great support from the community by providing facilities and infrastructure for FKPM such as meeting venue and office secretariat. Another indicator to the successfulness of FKPM is the growing of social capital in the community which was once destroyed because of the intervention of government policy in the â€œOrde baruâ€ regime. Keywords: community policing, civil police